Impact of postharvest management practices on the microbiome of blueberry from Tucumán, Argentina - María Florencia Perez; Florencia Isabel Chacón; Pedro Eugenio Sineli; Anja Poehlein; Rolf Daniel; Julián Rafael Dib (Journal of Agriculture and Food Research)
Blueberry (Vaccinium corymbosum L.) fruits harbor a unique microbiome that plays a crucial role in determining fruit quality, shelf life, and resistance to postharvest diseases. This microbiome, characteristic of each producing region, can be affected by various factors, including postharvest management practices. This study aimed to characterize the blueberry microbiome in Tucumán, Argentina, and evaluate the impact of postharvest processing. High-throughput sequencing was used to characterize bacterial and fungal communities in directly harvested blueberries (O) and commercial blueberries (C) subjected to washing, waxing, and cold storage. Directly harvested blueberries exhibited higher bacterial diversity, with ASVs associated to the genera Methylobacterium and Bacillus identified as potential biomarkers, highlighting their potential roles in plant health and biocontrol. In contrast, commercial blueberries showed increased fungal diversity, including ASVs associated to cold-tolerant pathogens like Botrytis caroliniana and beneficial yeasts such as Vishniacozyma victoriae and Sporobolomyces roseus, which may have applications in biocontrol and functional food development. This study demonstrated that postharvest practices significantly influence microbial diversity and composition, revealing potential microbial biomarkers that reflect regional production conditions and handling strategies. These results illustrate the need for microbiome-based approaches to optimize postharvest practices, balancing pathogen suppression with the promotion of beneficial microorganisms to preserve fruit quality and safety.